Microwave assisted synthesis of Dy2Ti2O7 ultrafine powders by sol–gel method. Issue 9 (July 2016) - Yu, Jincheng; Liu, Xiaojun; Ma, Li; Zheng, Haijiao; Zhang, Yubai; Gao, Dezhi; Gong, Hongyu; Zhang, Yujun
Abstract: Dy2 Ti2 O7 ultrafine powders ranging from 100 to 300 nm were successfully synthesized by sol–gel method. Particularly, the dried gel precursor was treated at different temperatures (700–1000 °C) via microwave-heating, which contributed to decreasing the grain size and reaction time. The phase composition and structural evolution of the final products were examined by X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM). Furthermore, the resultant powders were selected to fabricate ceramics and rubber based absobers. Their sinterability, mechanical properties and neutron absorption ability were also studied. Results showed that the highest flexural strength of 99.0 MPa were obtained for Dy2 Ti2 O7 samples when sintered at 1600 °C for 2 h in air atmosphere. Meanwhile, the neutron absorption rate of Dy2 Ti2 O7 ceramics and rubber based absorbers could reach 97.39% and 80.00% respectively when the thickness of samples was set as 5.0 mm.